Cyst Torsion in Mature Cystic Ovarian Teratoma: A Case Report - Singh, Karnel (Jurnal EduHealth, 2024)
Mature cystic teratoma is an ovarian germ cell tumor with the highest prevalence in women of reproductive age. Approximately 20% of patients are asymptomatic when the tumor is found. Acute pain may occur when there are complications. Echogenic nodules characterized by echogenic sebaceous substance and calcifications are the most common ultrasonographic findings. Generally, cystectomy is safe and effective in preserving ovarian function. Laparotomy and oophorectomy may be considered in cases with high risk of malignancy. The objective of this case report is to discuss a case of cyst torsion in an adult cystic ovarian teratoma, including its diagnosis and management. We report a case of cyst torsion in mature cystic ovarian teratoma in a 26-year-old woman with initial complaints of abdominal pain. The patient presented with complaint of abdominal pain 2 days before admission. There was a palpable mobile and painful mass in the lower left abdomen. Ultrasonography examination showed a cystic image of 11.6 cm x 7.2 cm x 9.3 cm with calcification. Left ovarian torsion was found intraoperatively, thus unilateral left salpingo-oophorectomy was performed with additional pathological results showing a mature cystic teratoma. The specimen was sent to the anatomical pathology confirming a mature cystic teratoma. ANC examination should not only focus on the fetus and uterus, but also require assessment of bilateral adnexa. Salpingo-oophorectomy can be avoided if detection can be done earlier.